A Cross-sectional Study of Parental, Peer, and Cigarette Advertising Influences on Smoking Behavior Among Adolescent Boys - Taqwin Taqwin; Moh. Ricki H.R. Djuga; Jurana; Amir; Nurlailah; Nasrul; Anna Veronica Pont; Azizah Saleh; Selvi Alfrida Mangundap; Baharuddin Condeng; Rina Tempake (Lentora Nursing Journal, 2026)
The Government of the Republic of Indonesia has made various efforts to reduce the number of adolescent boys who smoke. However, the number of adolescent male smokers continues to be high. This study aimed to identify the relationship between parental smoking, peer pressure, and exposure to tobacco advertising and smoking behavior among adolescents. This study was designed as a cross-sectional study with a sample of 55 male SMKN 6 Palu students, selected using proportional random sampling. Data collection was conducted using questionnaires and data analysis through chi-square tests and prevalence ratio (PR). The results of this study showed that the prevalence of adolescent smoking was at the level of 83.6%, most respondents were not affected by parental smoking (94.5%), 56.4% were influenced by friends who smoked, and 60% were influenced by exposure to tobacco advertisements. The chi-square test showed no significant association between smoking parents and adolescent smoking behavior (ρ=0.431); peer influence (ρ=0.957), and cigarette ad exposure (ρ=0.074) PR 1.25 (95% CI: 0.95–1.65). These findings indicate that none of the examined factors were statistically associated with adolescent smoking behavior, suggesting that the study hypothesis was not supported. Although a high prevalence of smoking and considerable exposure to cigarette advertising were observed, the results should be interpreted with caution and do not provide sufficient evidence to justify causal claims or strong policy recommendations. Further studies with larger samples and stronger designs are needed to clarify these relationships.